Postharvest handling of tropical produce: a training guide. Harvesting and Field Handling - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Miscellaneous Publications (IICA) no. 87-03